2004
DOI: 10.1111/j.1541-1338.2004.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Poverty with Mobility: A Normative Policy Analysis1

Abstract: Concentrated urban poverty is America's deepest social problem. Eliminating it stands as our nation's greatest challenge. In this article I analyze from a normative perspective antipoverty policies that attempt to address this problem via "mobility," that is, policies that attempt to disperse the urban poor to suburban locations. I find these policies to be normatively problematic on two grounds: the level coercion experienced by (and the corresponding lack of free choice given) a vulnerable population and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Yet, when considering how the exercise of choice might be made more “real,” all of the policies she advocates involve expanding exit options, such as expanding “the number and scale of assisted housing mobility initiatives” (i.e., Gautreaux/MTO‐type measures) and removing “regulatory and administrative barriers that now make it difficult for families to move between jurisdictions” (Turner, 1998: 388; also see Katz & Turner, 2001). In short, the zeal to push dispersal seems to blind Turner (1998) to the reality that exercising, in her words, “real choice about where to live” also includes enhancing the choice to live in one's current neighborhood by making such neighborhoods more livable (see Imbroscio, 2004b).…”
Section: Six Crimes Of Passion In Search Of a Policy Agendamentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, when considering how the exercise of choice might be made more “real,” all of the policies she advocates involve expanding exit options, such as expanding “the number and scale of assisted housing mobility initiatives” (i.e., Gautreaux/MTO‐type measures) and removing “regulatory and administrative barriers that now make it difficult for families to move between jurisdictions” (Turner, 1998: 388; also see Katz & Turner, 2001). In short, the zeal to push dispersal seems to blind Turner (1998) to the reality that exercising, in her words, “real choice about where to live” also includes enhancing the choice to live in one's current neighborhood by making such neighborhoods more livable (see Imbroscio, 2004b).…”
Section: Six Crimes Of Passion In Search Of a Policy Agendamentioning
confidence: 99%
“…Including this context transforms our understanding of the behavior of assisted mobility participants from an exercise of choice to a reaction to coercion 17 . Preferences for dispersal become nothing more than a desperate response to a set of desperate conditions, with little to do with any real notion of freedom of choice (Imbroscio, 2004b). 18 Correcting for this distortion, Frug (1999: 173) offers a more complete conception of the urban poor's “freedom of choice.” This conception, he writes, “supplements the freedom [of choice] to move with the freedom [of choice] to stay put—a freedom possible only if fear of violence and concern about bad schools no longer compel people to move, if they can, whether they want to or not ” (emphasis added).…”
Section: Six Crimes Of Passion In Search Of a Policy Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Their decisions become nothing more than "a desperate response to a desperate set of conditions with little to do with any real notion of freedom of choice" (Imbroscio, 2004;Imbroscio, 2008, 115). Galster and Mikelsons (1995) Galster (1996), and Reid (2007 extrapolate the geography of opportunity hypothesis and the linkages between geography and opportunity into the metropolitan opportunity structure, which is the set of institutions, markets, social and administrative systems and networks, and the individual's perception of the structures available to them, influenced by geography, that impacts an individual's socioeconomic mobility.…”
Section: Hope VI Impactsmentioning
confidence: 99%
“…First, the theory of spatial mismatch and empirical finding indicated that poverty was positively related to the lack of physical accessibility to economic opportunities (Holzer, 1991). Since housing mobility programs could bridge the gap between low-skilled workers and low-skilled jobs in suburbs, housing mobility programs were considered the best solution to fight poverty by many urban scholars (Imbroscio, 2004b(Imbroscio, , 2006.…”
Section: Program Theories Of Housing Mobility Programsmentioning
confidence: 99%